Linking mentoring within a community of practice to positive youth development among participants of a youth leadership program in Malaysia - Arshad, Mohd Mursyid; Ismail, Ismi Arif; Suandi, Turiman; Omar, Zoharah (Human Resource Management Academic Research Society, 2017)
Youth leadership is an element critically needed in nation building agenda. The involvement of new youth leadership talent can be enhanced through wider exposure and professional training, including via mentoring. This paper discusses the potential of mentoring on positive youth development through the help of the communities of practice (COP) in a youth leadership development program. The study was conducted using a qualitative approach informed by the case study paradigm. This study found that mentoring provides opportunity to communicate directly between protégé and mentor and allowing learning through the organizational members. In conclusion, protégé is not only limited to the mentor, but learning process also occurred through organizational members. The qualitative findings provide insight that mentoring clearly has the potential to constitute the process of leadership learning through the COP and provide the opportunity for youth to learn to become better leaders and better individuals.